The Transcriptomic Analysis of Circulating Immune Cells in a Celiac Family Unveils Further Insights Into Disease Pathogenesis - Ciccocioppo, Rachele; Panelli, Simona; Conti Bellocchi, Maria C.; Cangemi, Giuseppina C.; Frulloni, Luca; Capelli, Enrica; Corazza, Gino R. (Frontiers in Medicine, 2018)
Celiac disease (CD), the most common chronic enteropathy worldwide, is triggered and sustained by a dysregulated immune response to dietary gluten in genetically susceptible individuals. Up to date either the role of environmental factors and the pathways leading to mucosal damage have been only partially unravelled. Therefore, we seized the unique opportunity to study a naturally-occurring experimental model of a family composed of both parents suffering from CD (one on a gluten-free diet) and two non-celiac daughters. The control group consisted in four unrelated cases, two celiac and two non-celiac subjects, all matching with family members for both disease status and genetic susceptibility. In this privileged setting, we sought to investigate gene expression in peripheral blood mononuclear cells (PBMCs), a population known to mirror the immune response state within the gut. To this purpose, PBMCs were obtained from the four biopsied-proven CD patients and the four non-celiac cases. Each group included two family members and two unrelated control subjects. After RNA purification and cDNA synthesis, each sample underwent a microarray screen on a whole-transcriptome scale, and the hybridization results were visualized by hierarchical clustering. Differentially expressed genes (DEG) were partitioned into clusters displaying comparable regulations among samples. These clusters were subjected to both functional and pathway analysis by using the Kyoto Encyclopedia of Genes and Genomes. Interestingly, on a global gene expression level, the family members clustered together, regardless of their disease status. A relevant fraction of DEG belonged to a limited number of pathways, and could be differentiated based on disease status: active CD versus treated CD and CD versus controls. These pathways were mainly involved in immune function regulation, cell-cell junctions, protein targeting and degradation, exosome trafficking, and signal transduction. Worth of noting, a small group of genes mapping on the male-specific region of the Y chromosome, and previously linked to cardiovascular risk, was found to be strongly upregulated in the active CD case belonging to the family, who suddenly died of a heart attack. Our results provide novel information on CD pathogenesis and may be useful in identifying new therapeutic tools and risk factors associated with this